EKSISTENSI BADAN PENGAWAS PEMILIHAN UMUM DALAM PENYELENGGARAN PEMILIHAN UMUM MENURUT UU NOMOR 7 TAHUN 2017 TENTANG PEMILIHAN UMUM - Siti Mardiyati; Indrajaya Indrajaya (Universitas Muhammadiyah Kotabumi, 2021)
As one of the election organizers, Bawaslu has now become an institution that structurally already exists at the district and/or city level. As an institution authorized by law. Law Number 7 of 2017 concerning General Elections provides reinforcement for Bawaslu in carrying out prevention and prosecution with the authority to decide disputes over the election process and administrative violations. The problem in this journal research is how the existence of Banwaslu after the issuance of Number 7 of 2017. This type of legal research is normative, the legal materials used are primary, secondary and tertiary. It is carried out with a statute approach and the conclusion of this study is that the existence of Bawaslu is currently in line with public expectations